Tailored Treatment Strategies in First Line Therapy for Ovarian Cancer Patients: A Critical Review of the Literature - Daniela Luvero; Roberto Angioli; Federica Celoro; Francesco Plotti; Corrado Terranova; Federica Guzzo; Gianna Barbara Cundari; Federico Liparulo; Camilla Verdone; Roberto Montera (MDPI AG, 2024)
Background: Ovarian cancer (OC) is a significant cause of cancer-related mortality in women globally, with a five-year survival rate of approximately 49%. Standard therapy involves cytoreductive surgery followed by chemotherapy. Its poor prognosis has driven interest in alternative therapies such as targeted molecular agents like bevacizumab and poly (ADP-ribose) polymerase inhibitors (PARPi). Materials and Methods: This review systematically searched PubMed from January 2018 to December 2023 for studies on PARPi in OC. Emphasis was on identifying relevant Phase III trials, extracting data on study design, patient demographics, and outcomes. Special focus was on assessing PARPi efficacy, safety, impact on quality of life, and ongoing trials, including those on Clinicaltrials.gov. Results: The efficacy of PARPi in first-line therapy for OC has been extensively studied. Trials like SOLO-1, PRIMA, and ATHENA-MONO have demonstrated significant improvements in progression-free survival (PFS) and overall survival (OS), particularly in patients with BRCA mutations. Additionally, the combination of PARPi with other agents like bevacizumab has shown promising results in extending PFS. However, PARPi treatment is associated with various adverse effects, including hematologic toxicities like anemia, thrombocytopenia, and neutropenia. While most adverse events are manageable, some patients may require dose adjustments or discontinuation of treatment. Importantly, PARPi maintenance therapy has not adversely affected health-related quality of life (HRQoL), with studies reporting similar HRQoL scores between PARPi-treated and placebo-treated patients. Conclusions: PARPi offer effective treatment with manageable side effects, suitable even for medically fragile patients. Individualized dosing can optimize benefits while minimizing adverse events. Exploring diverse treatment approaches, particularly in patients with limited life expectancy or high disease burden, could improve outcomes. Ongoing research is investigating alternative therapies and combinations to broaden treatment options. Combining bevacizumab with PARPi may be justified for first-line and recurrent maintenance therapy. Regardless of mutational status, PARPi should be considered for maintenance therapy in newly diagnosed advanced OC. Platinum sensitivity remains crucial for treatment decisions and predicting survival outcomes.